Srpski - Stanković, Jelena (Glasnik Advokatske komore Vojvodine, 2022)
ABSTRACT: In this paper, the author has paid attention to the study of an extraordinary legal remedy, which represents a special barrier to legality. The principle of legality is one of the basic principles on which the legal system is based, which helps to achieve the basic goal of criminal procedure, ie that no innocent person is convicted, and that the perpetrator is sentenced under the conditions prescribed by criminal law. and a fairly conducted procedure, thus the request for protection of legality, as an extraordinary legal remedy gained in importanceThe subject of the paper is the analysis of theoretical understandings, positive legal solutions in the criminal procedure legislation of the Republic of Serbia, as well as the application of the requirement for protection of legality in practice, bearing in mind that the requirement for protection of legality has undergone major changes. in such situations, the case law deserves special attention, because it will play a key role.Key words: criminal procedure, legal remedy, extraordinary legal remedy, request for protection of legality